Abordaje y diagnóstico terapéutico del síndrome hepatorrenal. - Núñez Mariño, Hugo Jónathan (2023)
Hepatorenal syndrome (HRS) is a complication of liver cirrhosis that occurs with reversible acute kidney injury due to altered renal tissue perfusion. The severe deterioration of renal function in these patients is due to increased splanchnic blood flow and vasoconstriction of the renal vessels resulting in hypoperfusion of the renal vessels. Diagnosis remains a great challenge because there are no specific biomarkers for the pathology, so a diagnosis by exclusion is proposed, mainly with acute tubular necrosis (ATN). The clinical presentation of a hepatorenal patient is not specific but presents symptoms congruent with severe liver failure. Laboratory or imaging tests have not been established as diagnostic protocols; however, several paraclinical tests have been proposed to help in their exclusion. Neutrophil gelatinase-associated lipocalin (NGAL) is one of the most relevant biomarkers of acute kidney injury that allows the exclusion of other pathologies that share clinical renal involvement. Glomerular filtration rate and continuous evaluation of serum creatinine levels should be determined as a control parameter to determine the efficacy of the implemented treatment. Ultrasound measurement of renal vein collapse helps in the determination of volemia and the efficacy of volume expansion to avoid volume overload. The pharmacological treatment of first choice is terlipressin in combination with albumin, however, where there is no access to the drug, norepinephrine in combination with albumin can be substituted.